An environmental evaluation methodology for improving resource allocation decisions : a treatise with selected South African case studies - Stauth, Roy Bryan (Department of Environmental and Geographical Science, 2016)
This dissertation addresses the problem of how to manage environmental resources to improve the prospects that resource allocation activities will make the greatest possible contribution to social well-being. The study had two major aims. One aim was to provide a rational philosophical framework for guiding resource evaluation and decisionmaking processes. The second - and principal - aim was to develop a reliable and practical method for evaluating those resource allocation proposals which are particularly controversial. As part of the philosophical framework, a modification of the social welfare function is specified which explicitly addresses the well-being of future generations. This form of the social welfare function is based on certain a priori premises, which are used to define the goal and objectives of resource allocation, and to identify appropriate evaluation criteria. These evaluation criteria are then used to devise a resource management strategy and to develop an environmental evaluation methodology to serve that strategy. The methodology consists of both formal and informal methods of evaluation, but special attention is given to developing a formal method of evaluation that is simple and inexpensive to apply, and therefore particularly suited for Third World conditions. The principal research objective was to develop a useful method for evaluating those resource allocation proposals which are especially controversial. The method that has been developed - the Panel Evaluation Method - utilizes a cost-benefit framework and employs procedures modeled on the Delphi Method. The Panel Evaluation Method features three techniques for accomplishing a formal evaluation of competing proposals: the Impact Identification Technique is used to identify and define all the impacts of concern; the Significance Measurement Technique is used to judge the relative significance of the impacts; and the Criteria Trade-off Technique is used to determine which proposal best satisfies specified evaluation criteria. The Panel Evaluation Method was applied to several case studies with positive results. For example, the central feature of the method - the Significance Measurement Technique - was found to be capable of producing reasonably replicable results, and so is considered to provide an acceptable way to determine whether the costs of a proposal would exceed its benefits. The method thus serves to extend the capabilities of both Environmental Impact Assessment and Cost-benefit Analysis, and to link these two widely-used tools for guiding resource allocation decisions into a more powerful and versatile decisionmaking tool.